CD10-positive myoepithelial cells are usually prominent around in situ lobular neoplasia of the breast and much less prominent or absent in DCIS. Issue 8 (9th February 2016) - Shousha, Sami; Forbes, Georgina; Hopkins, Ilona; Wright, Josephine Anne
Abstract : Aims: To study the relationship between the neoplastic cells of in situ lobular neoplasia (ILN) and ductal carcinoma in situ (DCIS) and the surrounding CD10-positive myoepithelial cells. Materials and methods: Twenty consecutive cases of ILN and 51 of DCIS were stained for CD10 using the immunoperoxidase technique. The presence of CD10-positive cells was assessed semiquantitatively on a scale of 0–3 where 0 indicates their absence and 3 indicates the presence of multiple layers, which can be focal. Results: Ninety per cent of ILN cases scored 3, compared with none of DCIS (p=0.0001). There was a significant relationship between DCIS grade and CD10 score, with the mean scores being 1.43, 0.82 and 0.5 for low, intermediate and high grade, respectively. CD10-positive cells were always present around low-grade DCIS, but absent in 27% of high-grade cases. CD10-positive cells were more frequent in ER-positive than in ER-negative DCIS, and in HER2-negative than in HER2-positive cases, but the difference was not statistically significant. Conclusions: There is a distinct relationship between the type and grade of in situ neoplasia of the breast and the surrounding CD10-positive myoepithelial cells, suggesting the presence of a 'cross talk' between the two elements.